Code-switching in blogs of older and younger Malaysian Chinese / Angelina Wong Li Wei - Wong, Angelina Li Wei (2012)
Code-switching is a common occurrence in a multilingual country like Malaysia. Over the years, researches have been conducted to study oral code-switching in multilingual societies. However, the emergence of weblogs or better known as blogs is changing the way people interact over the Internet. Code-switching is noted to take place in online emails, journals, chatrooms, emails and also blogs. This study aims to investigate the domains in which code-switching takes place more often can be discovered as well as the similarities and differences in the writing of blogs between two age groups (older and younger) of Malaysian Chinese female bloggers. Data was collected over the period of one month and analyzed to identify the differences and similarities in the styles and patterns throughout August 2010. The frequency of which code-switching took place in their entries were tabulated and further discussed for better understanding. Reasons that triggered these code-switchings were identified. The findings of the study proved that Fishman‘s (1972) findings on topics of code-switching also occur in blogs. Furthermore, the result did show vast differences between the styles and patterns used by these two groups of bloggers.